The Plantation Forestry Sector in Mozambique : Community Involvement and Jobs - Serzedelo de Almeida, Leonor (World Bank, Washington, DC, 2019)
Mozambique had 60,000 hectares of large-scale commercial planted forest in 2009, supporting about 3,000 full-time-equivalent jobs. Very little growth in large-scale commercial planted area has occurred since 2009, unlike what would be required to meet predictions at the time of 1,000,000 hectares planted by 2030. Labor costs are three to four times lower in plantation forestry in Mozambique than in Brazil, South Africa, and Uganda. Yet, unit costs per cubic meter of eucalyptus timber produced in Mozambique are higher due to lower tree volume growth rates, skills gaps, and employee absenteeism up to 50 percent. Yet, deforestation and imports of high-end wood products are rekindling interest in plantation forestry, with recognition of the need for community involvement. Integration of smaller-scale forestry into community land use patterns is taking off. Recommended actions include: matching grants financed by public resources to leverage private investment and contract farming through community woodlots; empowerment of an independent third-party organization funded by companies to analyze, broker and communicate amongst relevant stakeholders; private sector mobile agroforestry schools for training in remote areas; community land-use plans developed with local stakeholders, delimiting different kinds of land and different rights; and strengthening of community-based organizations that deal with land.